2002
DOI: 10.1016/s0020-7292(02)00092-9
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperglycemia and Adverse Pregnancy Outcome (HAPO) Study

Abstract: HAPO is a 5-year investigator-initiated prospective observational study that will recruit approximately 25000 pregnant women in 10 countries. HAPO utilizes a Central Laboratory for measurement of key metabolic variables, a Clinical Coordinating Center, a Data Coordinating Center, and an independent Data Monitoring Committee. Glucose tolerance is assessed by a 75 g 2-h OGTT at 24-32 weeks' gestation. Results are unblinded to the woman and her caregivers if: fasting plasma glucose >5.8 mmol/l, 2-h plasma glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(89 citation statements)
references
References 29 publications
3
86
0
Order By: Relevance
“…All participants gave written informed consent. Medical caregivers and participants were “blinded” to glucose tolerance test results, unless glucose values exceeded predefined thresholds, meriting further follow-up (12). For this secondary analysis, we limited the data to the 6,159 participants who had blinded data and who participated only through one of the North American centers (members of the HAPO Study Cooperative Research Group North American Field Centers: Kaiser Foundation Hospital, Bellflower, CA; Prentice Women’s Hospital of Northwestern Memorial Hospital–Northwestern University Feinberg School of Medicine, Chicago, IL; MetroHealth Medical Center–Case Western Reserve University, Cleveland, OH; Women and Infants’ Hospital of Rhode Island–Brown University Medical School, Providence, RI; Sunnybrook and Women’s College Health Sciences Centre–University of Toronto, Toronto, Ontario, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…All participants gave written informed consent. Medical caregivers and participants were “blinded” to glucose tolerance test results, unless glucose values exceeded predefined thresholds, meriting further follow-up (12). For this secondary analysis, we limited the data to the 6,159 participants who had blinded data and who participated only through one of the North American centers (members of the HAPO Study Cooperative Research Group North American Field Centers: Kaiser Foundation Hospital, Bellflower, CA; Prentice Women’s Hospital of Northwestern Memorial Hospital–Northwestern University Feinberg School of Medicine, Chicago, IL; MetroHealth Medical Center–Case Western Reserve University, Cleveland, OH; Women and Infants’ Hospital of Rhode Island–Brown University Medical School, Providence, RI; Sunnybrook and Women’s College Health Sciences Centre–University of Toronto, Toronto, Ontario, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…HAPO methods were described previously [11, 15]. Eligible women underwent a 75 g OGTT at 24–32 weeks gestation after an overnight fast of at least 8 h. Fasting (FPG) and 1 h plasma glucose were measured, and fasting and 1 h serum samples were stored at −80°C until the metabolomics assays.…”
Section: Methodsmentioning
confidence: 99%
“…To validate our seven most significant findings in the Cambridge cohorts we tested the same associations between maternal mean arterial blood pressures and the fetal imprinted gene alleles in 1,367 HAPO study participants 15, 16 of European descent whose single nucleotide polymorphism (SNP) genotypes were derived from a GWAS of maternal glycemic and neonatal anthropometric traits 17 . Study participant characteristics are shown in Table 1C.…”
Section: Methodsmentioning
confidence: 99%